Objective quantitative methods to evaluate microtia reconstruction: A scoping review - Yangyang Lin; Elsa M. Ronde; Kevin E.J. van den Brule; Nadia Lachkar; F.S. van Etten-Jamaludin; Theo H. Smit; Corstiaan C. Breugem (JPRAS Open, 2023)
Summary: Background: Commonly used methods to evaluate auricles are subjective and are therefore not specific, comprehensive, and precise nor effective in the assessment of microtia reconstruction outcomes. This scoping review aimed to summarize the objective methods for the accurate evaluation of microtia reconstruction. Methods: We performed a scoping review of publications that used objective measurement methods to evaluate outcomes of microtia reconstruction according to the PRISMA-ScR guidelines. A systematic literature search was conducted in the Embase, PubMed, Cochrane, CNKI, and VIP databases, and literature references were screened for additional records. Studies that evaluated auricles after microtia reconstruction using quantitative anthropometric methods were included, and data on these methods were collected. Results: Twenty-five publications reported on quantitative objective outcome measurements. Thirteen studies evaluated auricular protrusion, three articles assessed the position or symmetry, and twelve studies reported on auricle size. The quantitative measurements of fine structures, such as the tragus and concha, were described in three studies. All described measurements used manual landmarking, where fifteen studies described well-defined landmarks, fifteen studies described poorly defined landmarks, and four studies used a combination of well and poorly defined landmarks. Conclusion: The objective evaluation of microtia reconstruction outcomes is hindered by significant heterogeneity of measurement methods. The measurement methods used for general auricular measurements (auricular protrusion, auriculocephalic angle, and size) used in microtia reconstruction were abundant, while measurements of auricular position and the fine structures of the auricle were limited. Three-dimensional imaging combined with computer analyses poses promising future alternatives.